Impact of a dedicated multidisciplinary meeting on the management of superficial cancers of the digestive tract - Dermine, Solène; Barret, Maximilien; Prieux, Caroline; Ribière, Sophie; Leblanc, Sarah; Dhooge, Marion; Brezault, Catherine; Abitbol, Vered; Terris, Benoit; Beuvon, Frédéric; Rouquette, Alexandre; Dousset, Bertrand; Gaujoux, Sébastien; Soyer, Philippe; Dohan, Anthony; Bibault, Jean-Emmanuel; Coriat, Romain; Prat, Frédéric; Chaussade, Stanislas (Endoscopy International Open, 2018)
Background The recent development of endoscopic resection for superficial gastrointestinal cancers could justify the need for a dedicated oncological multidisciplinary meeting (MDM). The aim of our study was to evaluate the impact of the dedicated MDM on the management of superficial cancers of the digestive tract.Methods A dedicated MDM was developed at our tertiary referral center. A retrospective review of the MDM conclusions for all patients referred from March 2015 to March 2017 was performed. Outcomes measurements were the outcomes of endoscopic resection, and the concordance rate between the MDM recommendations, European Society of Gastrointestinal Endoscopy (ESGE) guidelines, and final patient management.Results In total, 153 patients with a median age of 69 years were included. Half of the patients had major comorbidities. The mean lesion size was 25 mm, and R0 and curative resection rate were 73.9 % and 56.9 %, respectively. Forty-three patients had an indication for surgery after endoscopic resection. The concordance rate between ESGE guidelines and MDM recommendation was 92.2 %, and 12 patients did not receive the treatment recommended due to comorbidities.Conclusion A MDM dedicated to superficial tumors helped tailor the ESGE guidelines to each patient in order to avoid unnecessary surgery.